Cytotoxic activity of Luvunga scandens against human cancer cell lines - Al Zikri, Putri Nurhidayah; Bakhtiar, M. Taher; Darnis, Deny Susanti; Arief Ichwan, Solachuddin Jauhari (Penerbit UTM Press, Universiti Teknologi Malaysia., 2016)
Luvunga scandens belongs to the family of Rutaceae which usually inhabit tropical and moist environment. This plant is known as ‘Mengkurat Jakun’ among locals and used traditionally to treat fever and fatigue via decoction. Purpose: The aim of this study was to investigate the cytotoxic activity of the leaves and stems extracts of L. scandens extract. Methods: Extracts of the leaves and stems were obtained from sequential extraction procedures by various organic solvents. All extracts were subjected to cytotoxic study by 3-(4, 5-dimethylthaizol-2-yl)-2, 5-diphenyltetrazolium bromide (MTT) assay. Results: In in vitro cytotoxicity assay, all L. scandens extracts exhibited cytotoxicity against human breast adenocarcinoma (MCF-7) and human lung adenocarcinoma (A549) cell lines. The IC50 values of dichloromethane and methanol extracts from the leaves of L. scandens against MCF-7 cell line were 62.5 µg/mL and 88.0 µg/mL, respectively, whereas IC50 of methanol extract from stem was 81.0 µg/mL. All extracts were less active against A549 cell line where IC50 value were not be determined. Conclusion: The present findings revealed the potential of L. scandens as a cytotoxic agent against MCF-7 cell line. However, further studies should be planned to evaluate role of the plant in cytotoxic activity.